Isolation and Identification of Fungal Species Contaminating the Refrigerators - Hiba Hadi Taha; Faten Noori Mula Abed; Jehaan Mowfak Al-Rawi (Al-Kitab Journal for Pure Sciences)
Refrigeration is one of the most widely used methods to control the growth of microorganisms in food products.  A number of isolates was 433, including 363 isolates from refrigeration and 70 isolates from freezers. The fungus Cladosporium sp. is the large number in both refrigeration and freezer, 187 and 28, respectively, and the lowest numbers of fungi such as Rhizopus stolonifer, Rhizoctonia solani, and Fusarium sp., many fungi were isolated from refrigeration, while fungal isolates from freezing were less numerous and less diverse. Molecular identification of Cladosporium sp. because it is the most frequent among the fungal isolated from refrigeration and freezing by using polymerase chain reaction, it has been shown that Cladosporium sphaerospermum strain HKA in the gene bank. The aim of the study is to recognize the fungi that contaminate the refrigerator both domestically and commercially.